Streaming success: positioning Roku's future in a hypercompetitive industry. Issue 3 (3rd July 2021) - Pleggenkuhle-Miles, Erin G.; Winchester, Christopher C.; Bass, A. Erin; West, Thomas
Abstract : Theoretical basis: The theoretical basis for this case is a focus on strategic positioning as related to Porter's Generic Strategies. The case accounts Roku's journey in facing additional competition, highlighting the competitive dynamics at play. The case requires students to consider how Roku might revise its generic strategy based on the new competitive landscape in which it operates. Research methodology: In writing this case, the research team used secondary research that was informed by interviews with Roku users. Resources such as IBIS World, MergentOnline, academic journals, trade magazines and websites were used to inform and verify information. Case overview/synopsis: As the market disruptor of how media was consumed, Roku had been connecting customers, publishes and advertisers with its unique capabilities for over 10 years. With the belief that all TV content should be available through streaming, Roku had forever changed the traditional model of how media was distributed and consumed. By capitalizing on the previously untapped economic opportunity of TV streaming platforms, Roku had made itself the premier streaming broadcast service for users, content publishers and advertisers. The company was now faced with the difficult task of finding the best ways to keep innovation high and continue to grow. Complexity academic level: This case could be taught at either the graduate or undergraduate level strategy course. At the undergraduate level, it would be best taught in a strategy course, when discussing industry life cycle or vertical integration. At the graduate level, MBAs could discuss the competitive dynamics and hypercompetition within the industry.